Doing without concepts - Machery, Edouard (Oxford : Oxford University Press, 2009)
In this work, Edouard Machery argues that the dominant psychological theories of concepts fail to provide a framework and that drastic conceptual changes are required to make sense of the research on concepts in psychology and neuropsychology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Concepts